Exceeding 50% injected lightning energy not sourced: During the analysis of an OGW rupture accident caused by multiple lightning strikes. (January 2023) - Liu, Gang; Guo, Deming; Lin, Ziming; Peng, Xiangyang; Lin, Xuan; Chen, Lyuwen; Wang, Rui; Lyu, Weitao
Highlights: OGW may also break due to the small lightning strikes when the arc root moves. When simulating the natural lightning strike, at least 66% energy is ignored. Sliding motion of lightning arc root causes long axial ablation length of OGW. Jumping motion of lightning arc root causes multiple lightning strike points. An analytical model describing the movement of lightning arc root is established. Abstract: Overhead ground wire (OGW) is erected to protect transmission conductors from lightning strikes. However, OGW can be damaged or even ruptured due to lightning strikes, which threatens the stable operation of the power system. Thus, it is necessary to study the lightning-induced damage or rupture mechanism to provide a theoretical guidance for the structure optimization or selection criteria improvement for OGW. In this paper, an OGW rupture accident due to lightning arc root movement under multiple return strokes was analyzed. Firstly, based on the evidence at the accident scene and the damage characteristics of the sample, it was preliminarily inferred that multiple lightning strike points caused the rupture of OGW in the accident. An analytical model simulating the lightning arc root movement was established to prove the existence of lightning arc root movement phenomenon in the accident. In addition, the thermal ablation model of OGW was also established according to the existing numerical methods. The differences between OGW damage results of model and sample were compared. The results of this paper showed that the sliding movement and jumping movement of the lightning arc root caused the long axial ablation length and multiple lightning strike points of OGW in the accident, respectively. Existing numerical methods as well as the laboratory generated lightning strikes experiments did not accurately calculate the thermal ablation damage of OGW caused by the natural lightning strikes. For this accident sample, at least 66% injected lightning energy is not considered when simulating the physical process of the natural lightning striking OGW. Based on the research result, simulation test of lightning strike should be considered before OGW is put into operation. Moreover, for the existing simulation test method of lightning strike, the injected lightning energy should also be increased.